Production Performance, Feed Efficiency and their Correlation in Lactating Kankrej Cows at Organized Farm - Gami, Y.M.; Patel, M.P.; Pawar, M.M.; Chaudhari, A.B.; Rathod, B.S.; Panchasara , H.H.; Patil , S.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A study was conducted to assess production performance, feed efficiency and their correlation in lactating Kankrej cows at organized farm. The variables such as average dry matter intake, milk yield, milk composition and feed efficiency were evaluated in 49 lactating Kankrej cows over a period of 30 days. The mean dry matter intake was 9.71±0.08 kg/d. The average milk yield and energy corrected milk were 12.45±0.35 kg/d and 14.27±0.47 kg/d, respectively. Feed efficiency was 1.48±0.05 in Kankrej cows, and it was significantly affected by average milk yield and energy corrected milk. The average milk yield and energy corrected milk were highly correlated with feed efficiency. Pearson’s square correlation coefficient was 0.96 between feed efficiency and energy corrected milk.
Keywords: Kankrej cow; milk yield; Correlation coefficient; dry matter intake; feed efficiency